KERENTANAN PENAMBAK GARAM AKIBAT PERUBAHAN MUSIM HUJAN DI DESA RANDUTATAH, KABUPATEN PROBOLINGGO - Wahyono, Ary (Jurnal Masyarakat dan Budaya, 2012)
This paper describes the vulnerability of salt farmers due to changes in rainy season caused by climate change. This paper also discusses about its effect on the working relationship between salt pond owners and salt farmers that need to adapt to this climate change or managing the risk sharing between parties. Salt farming is the main source of income of the people in coastal area in Probolinggo, East Java. The risk of salt pond harvest failure is relatively smaller than shrimp pond or fish pond. Salt pond farming is less like in to subject to crop disease or seed mortality, or any other problems that may happen on other farmings. Nonetheless, the salt farming at present faces difficulties since the global warming change the rainy season has changed. Usually the rainy and dry season was predictable, therefore the salt farmers are able to plan their income sources. Salt farming business is the activity conducted during dry season; and during rainy season, salt farmer work as crop workers, or fishermen. Unpredicted rainy season makes salt farmers unable to schedule salt farm production. The rain melts the salt, therefore the salt farmer has to start all over again. Keywords: climate change, social vulnerability, salt pond, salt farmer